Utilization of Iles-Iles and Sorghum Starch for Bioethanol Production - Kusmiyati, Kusmiyati; Sulistiyono, Agus (Center of Biomass & Renewable Energy (CBIORE), 2014)
The aims of this study were to convert the starches from iles-iles tubers (Amorphophalus campanulatus) and sorghum grains (Sorghum bicolor L) into bioethanol as an alternative energy. Both of these agricultural products contains a high content starches and they do not use as the major foods in Indonesia. To find out the maximum ethanol concentration and yield, both the raw materials were converted to ethanol on various process variables including the concentration of flour substrate solution (100-300 g/L), β-amylase enzyme concentration (0.8 - 6.4 ml/kg of flour ), the concentration of dry yeast S. cerevisiae (2-15 g), and fermentation time (72-168 hours). The results showed that at the flour substrate concentration of 250 g/L produced the maximum ethanol contents of 100.29 g/L and 95.11 g/L for iles-iles and sorghum, respectively. Effect of β-amylase enzyme in the saccharification process showed that at concentration of 3.2 ml/kg the maximum reducing sugar content of 204.94 g/L and 193.15 g/L for iles-iles and sorghum substrate, respectively were generated therefore it was corresponding to the maximum ethanol production. The concentration effect of dry yeast S. cerevisiae in the fermentation stage for the iles-iles and sorghum substrate revealed that the maximum ethanol obtained at 5 g yeast activated in 100 ml medium starter resulted the highest ethanol content 100.29 g/L 95.11 g/L for iles-iles and sorghum substrate, respectively. To determine the effect of fermentation time on ethanol yield from iles-iles and sorghum substrate, the fermentation process were performed at 3, 5, and 7 days. The maximum ethanol fermentation was obtained at 5 days fermentation. The ethanol yield is calculated by weight of ethanol is formed (g) divided by the weight of flour (g). Based on the experiment results, conducted, generally the highest ethanol yield of iles-iles was higher than that of sorghum flour. The highest yield (g/g) iles-iles and sorghum flour were 71.25 and 68.92 respectively